Analysis Of Green Accounting To Support Corporate Social Responsibility (Case Study : Semen Gresik Hospital) - Khoirina, Marisya Mahdia (UNIVERSITAS NEGERI SURABAYA, 2016)
AbstractThe Implementation of green accounting in hospital activities is the first step to solved environmental problems. Implementation of green accounting will work up the ability to minimize the environmental problem. The purpose of this accounting process is to improve the efficiency of environmental management by assessing environmental activities from a cost point of view (environmental cost). This research is a descriptive qualitative study using case studies method on Semen Gresik Hospital. This study aims to determine how to conduct environmental management and the application of the concept of green accounting. The research results revealed that Semen Gresik Hospital has not implemented the concept of green accounting yet. This can be seen in the identification of costs, there is no aspect of measurement and clear classification how a costs is categorized as environmental costs or not. The results also showed that the Semen Gresik Hospital had not made the environmental financial report.